Critical Behavior and Macroscopic Phase Diagram of the Monoaxial Chiral Helimagnet Cr1/3NbS2 - Eleanor M. Clements (Nature Portfolio, 2017)
Abstract Cr1/3NbS2 is a unique example of a hexagonal chiral helimagnet with high crystalline anisotropy, and has generated growing interest for a possible magnetic field control of the incommensurate spin spiral. Here, we construct a comprehensive phase diagram based on detailed magnetization measurements of a high quality single crystal of Cr1/3NbS2 over three magnetic field regions. An analysis of the critical properties in the forced ferromagnetic region yields 3D Heisenberg exponents β = 0.3460 ± 0.040, γ = 1.344 ± 0.002, and T C = 130.78 K ± 0.044, which are consistent with the localized nature the of Cr3+ moments and suggest short-range ferromagnetic interactions. We exploit the temperature and magnetic field dependence of magnetic entropy change (ΔS M) to accurately map the nonlinear crossover to the chiral soliton lattice regime from the chiral helimagnetic phase. Our observations in the low field region are consistent with the existence of chiral ordering in a temperature range above the Curie temperature, T C < T < T*, where a first-order transition has been previously predicted. An analysis of the universal behavior of ΔS M(T,H) experimentally demonstrates for the first time the first-order nature of the onset of chiral ordering.